Effects of lifestyle on physical health in Slovak university students - Duranková, Silvia; Csanády, Alexander; Ždiľová, Anna; Bernasovská, Jarmila; Buková, Alena (Anthropological Review, 2020)
Overweight and obesity in childhood and young people represent a large global health problem. Therefore, the main aim of the study was to assess the prevalence of overweight/obesity by body mass index (BMI) and its associated lifestyle factors among university students in Slovakia. The BMI index was examined in relation to nine life factors for both sexes, respectively, in a sample of 200 (108 men and 92 women) young university students from Slovakia. The data were obtained using anthropometric measurements and by means of a questionnaire. The results for BMI values confirmed that both sexes were classified into the “about right” weight category. Analysis of the BMI values and questionnaire data showed different results for both sexes. While the type of daily activity and type of physical activity were associated with greater obesity for men, in women, tobacco intake was an important.